Lithium iron phosphate positive electrode active material and preparation method thereof, positive electrode sheet, lithium secondary battery, and electrical equipment

By using high specific surface area modified materials to prepare bimodal distributed iron phosphate materials, the problem of insufficient compaction density of lithium iron phosphate positive electrode active materials is solved, high compaction density and excellent rate performance are achieved, and the needs of long range and large capacity, high energy-efficiency and long cycles are met.

CN119764419APending Publication Date: 2025-04-04DANGSHENG SHUDAO (PANZHIHUA) NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996911.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The compaction density of existing lithium iron phosphate positive electrode active materials cannot meet the needs of long range and large capacity, high energy efficiency and long cycles.

Method used

A modified material with a large specific surface area is used to provide a growth frame when preparing iron phosphate, and a bimodal distribution of iron phosphate material is obtained through two sintering processes, thereby preparing lithium iron phosphate positive electrode active material with high compaction density and excellent rate performance.

Benefits of technology

The high compaction density, excellent rate performance, high gram capacity and excellent cycle performance of lithium iron phosphate-type positive electrode active materials are achieved, which simplifies production steps and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764419A_ABST
    Figure CN119764419A_ABST
Patent Text Reader

Abstract

The present application proposes a lithium iron phosphate positive electrode active material and a preparation method thereof, a positive electrode sheet, a lithium secondary battery, and an electrical device. The lithium iron phosphate positive electrode active material includes a compound shown in formula I: Li a M 1‑b Me b P c O4 / C formula 1, wherein 0.9≤a≤1.1, 0.98≤b<1, 0.96≤b / c≤0.99, Me includes at least one element of Mn, Co, Ni, and Fe, and M includes at least one element of W, Mg, Nb, V, Ti, Mo, Rh, Os, and Ta; the D50 of the lithium iron phosphate positive electrode active material is 0.9μm-1.3μm, and the compaction density of the lithium iron phosphate positive electrode active material is 2.58g / cm 3 ‑2.64g / cm 3 Thus, a lithium iron phosphate-based positive electrode active material having a high compaction density and excellent rate performance is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and specifically, to lithium iron phosphate-based positive electrode active materials and preparation methods thereof, positive electrode sheets, lithium secondary batteries, and electrical equipment. Background Art

[0002] Lithium iron phosphate has become one of the main cathode active materials currently used due to its high safety, long cycle life, low cost, wide source of raw materials, and environmental friendliness. It has been popular in the market, especially after the launch of blade battery technology. Since its shipments surpassed ternary materials in 21 years and gradually gained recognition from international downstream companies, it has maintained its leading advantage. In particular, the rapid development of the energy storage industry has further promoted the expansion of lithium iron phosphate, and finally formed a 7:3 pattern with ternary materials. With people's increasing pursuit of long endurance (power) and large-capacity, high-efficiency and long-cycle (energy storage), the compaction density of lithium iron phosphate cathode active materials in related technologies cannot meet the demand. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0004] In a first aspect, the present application provides a lithium iron phosphate positive electrode active material, including a compound shown in formula I:

[0005] Li a M 1-b Me b P c O4 / C formula 1,

[0006] Wherein, 0.9≤a≤1.1, 0.98≤b<1, 0.96≤b / c≤0.99, Me includes at least one element selected from Mn, Co, Ni, and Fe, and M includes at least one element selected from W, Mg, Nb, V, Ti, Mo, Rh, Os, and Ta;

[0007] The D50 of the lithium iron phosphate positive electrode active material is 0.9 μm-1.3 μm, and the compaction density of the lithium iron phosphate positive electrode active material is 2.58 g / cm 3 -2.64g / cm 3 The lithium iron phosphate positive electrode active material proposed in the present application has a high compaction density and excellent rate performance.

[0008] The second aspect of the present application provides a method for preparing the lithium iron phosphate positive electrode active material provided in the first aspect of the present application, the method comprising: mixing an iron source solution, a phosphoric acid solution, an oxidant, and a modifying material to obtain a first slurry, wherein the specific surface area of ​​the modifying material is 1200 m 2 / g-1600m 2 / g, the modified material includes at least one of activated carbon, graphene, and covalent organic framework materials; the first slurry is heated and dried to obtain a first intermediate product; the first intermediate product is sintered for a first time and crushed to obtain the iron phosphate; the iron phosphate, lithium source, carbon source, additive, and solvent are mixed to form a second slurry, which is dried to obtain a second intermediate product; the second intermediate product is sintered for a second time under a protective atmosphere, the temperature of the second sintering is greater than the temperature of the first sintering, and crushed to obtain the lithium iron phosphate positive electrode active material.

[0009] The method for preparing lithium iron phosphate positive electrode active materials proposed in the present application uses a modified material with a large specific surface area when preparing iron phosphate, which can provide a growth framework for the synthesis of iron phosphate. After the first sintering, an iron phosphate material with a bimodal distribution is obtained. Different from the traditional bimodal distribution, the bimodal distribution of the present application is caused by the microstructural differences of the primary particles. When preparing lithium iron phosphate positive electrode active materials, the iron phosphate having the above structure can form a lithium iron phosphate positive electrode active material with a higher pressure chamber density and a higher gram capacity.

[0010] According to some embodiments of the present application, the specific surface area of ​​the modified material is 1200 m 2 / g-1400m 2 / g.

[0011] According to some embodiments of the present application, based on the total mass of the first slurry, the mass proportion of the modified material is 0.1%-0.3%.

[0012] According to some embodiments of the present application, the activated carbon includes 800-1500 mesh activated carbon; and / or the covalent organic framework material includes at least one of COF-5 and CTF-1.

[0013] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the heating temperature is 80°C-90°C, and the heating time is 2h-5h; the first sintering temperature is 500°C-700°C, and the first sintering time is 2h-5h.

[0014] According to some embodiments of the present application, the method for obtaining the iron source solution includes: mixing an untreated iron source solution, a phosphorus source solution, and a flocculant to obtain a pretreated mixed solution, adjusting the pH of the pretreated mixture to 2-4, filtering the precipitate, and obtaining the iron source solution, wherein the molar concentration of iron in the iron source solution is 1.5 mol / L-2 mol / L.

[0015] According to some embodiments of the present application, the molar ratio of phosphorus element to iron element in the first slurry is 1.1-1.25.

[0016] According to some embodiments of the present application, the iron phosphate satisfies at least one of the following conditions: the volume average particle size Dv50 of the iron phosphate is 2μm-10μm; the particle size distribution diagram of the iron phosphate presents a bimodal distribution; the Fe / P of the iron phosphate is 0.95-0.99.

[0017] According to some embodiments of the present application, the temperature of the second sintering is 720° C.-820° C., and the time of the second sintering is 20 h-30 h.

[0018] The third aspect of the present application provides a positive electrode plate, comprising the lithium iron phosphate type positive electrode active material provided in the first aspect of the present application or the lithium iron phosphate type positive electrode active material prepared by the method provided in the second aspect of the present application.

[0019] The fourth aspect of the present application provides a lithium secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.

[0020] The fifth aspect of the present application provides an electrical device, including the lithium secondary battery provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0022] Figure 1 A schematic diagram of a process for preparing a lithium iron phosphate positive electrode active material according to an embodiment of the present application is shown.

[0023] Figure 2 The SEM image of the iron phosphate prepared in Example 1 of the present application is shown.

[0024] Figure 3 The SEM image of the cross section of the iron phosphate prepared in Example 1 of the present application is shown.

[0025] Figure 4 The SEM image of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present application is shown.

[0026] Figure 5 The SEM image of the iron phosphate prepared in Example 2 of the present application is shown.

[0027] Figure 6 The SEM image of the cross section of the iron phosphate prepared in Example 2 of the present application is shown.

[0028] Figure 7 The SEM image of the lithium iron phosphate positive electrode active material prepared in Example 2 of the present application is shown.

[0029] Figure 8The SEM image of the iron phosphate prepared in Example 3 of the present application is shown.

[0030] Fig. 9 The SEM image of the lithium iron phosphate positive electrode active material prepared in Example 3 of the present application is shown.

[0031] Fig.10 The particle size distribution diagram of the iron phosphate prepared in Examples 1 to 3 of the present application is shown.

[0032] Fig.11 The SEM image of the iron phosphate prepared in Comparative Example 1 of the present application is shown.

[0033] Fig.12 The SEM image of the cross section of the iron phosphate prepared in Comparative Example 1 of the present application is shown.

[0034] Fig.13 The SEM image of the lithium iron phosphate positive electrode active material prepared in Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION

[0035] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0036] In a first aspect, the present application provides a lithium iron phosphate positive electrode active material, including a compound shown in formula I:

[0037] Li a M 1-b Me b P c O4 / C formula 1,

[0038] Wherein, 0.9≤a≤1.1, 0.98≤b<1, 0.96≤b / c≤0.99, Me includes at least one element selected from Mn, Co, Ni, and Fe, and M includes at least one element selected from W, Mg, Nb, V, Ti, Mo, Rh, Os, and Ta;

[0039] The D50 of the lithium iron phosphate positive electrode active material is 0.9 μm-1.3 μm, and the compaction density of the lithium iron phosphate positive electrode active material is 2.58 g / cm 3 -2.64g / cm 3 The lithium iron phosphate positive electrode active material proposed in the present application has a high compaction density and excellent rate performance.

[0040] In the present application, the test method for the compaction density of the lithium iron phosphate positive electrode active material is: prepare 1g of sample, put it into a mold with a diameter of 13mm, use the Sansi Zongheng (UTM7305) compaction density meter, adjust the dynamometer pressure to 3KN, maintain the pressure for 30s, and then obtain the compaction density of the sample.

[0041] According to some embodiments of the present application, the compaction density of the lithium iron phosphate positive electrode active material can be 2.58 g / cm 3 , 2.6g / cm 3 , 2.62g / cm 3 , 2.64g / cm 3 The above-mentioned arbitrary numerical ranges may also be used.

[0042] As an example, a may be 0.9, 0.95, 1, 1.05, 1.1, etc., or may be a range consisting of any of the above values.

[0043] It should be noted that in the positive electrode sheet, battery or electrical device, as the battery undergoes formation and circulation processes, lithium ions will be consumed, so the measured lithium content x in the positive electrode active material may be less than 1. At the same time, if the positive electrode sheet and the negative electrode sheet use a lithium supplement, after the battery undergoes formation and circulation processes, the measured lithium content x in the positive electrode active material may be greater than 1.

[0044] As an example, b may be 0.98, 0.985, 0.99, 0.995, 1, etc., or may be a range consisting of any of the above values.

[0045] As an example, b / c may be 0.96, 0.97, 0.98, 0.99, etc., or may be a range consisting of any of the above values.

[0046] The second aspect of the present application provides a method for preparing the lithium iron phosphate positive electrode active material provided in the first aspect of the present application, the method comprising: mixing an iron source solution, a phosphoric acid solution, an oxidant, and a modifying material to obtain a first slurry, wherein the specific surface area of ​​the modifying material is 1200 m 2 / g-1600m 2 / g, the modified material includes at least one of activated carbon, graphene, and covalent organic framework materials; the first slurry is heated and dried to obtain a first intermediate product; the first intermediate product is sintered for a first time and crushed to obtain the iron phosphate; the iron phosphate, lithium source, carbon source, additive, and solvent are mixed to form a second slurry, which is dried to obtain a second intermediate product; the second intermediate product is sintered for a second time under a protective atmosphere, the temperature of the second sintering is greater than the temperature of the first sintering, and crushed to obtain the lithium iron phosphate positive electrode active material.

[0047] The method for preparing lithium iron phosphate positive active materials proposed in this application uses a modified material with a large specific surface area when preparing iron phosphate, which can provide a growth framework for the synthesis of iron phosphate. After the first sintering, an iron phosphate material showing a bimodal distribution is obtained. Different from the traditional bimodal distribution, the bimodal distribution of this application is a bimodal distribution caused by the microstructural difference of the primary particles. When preparing lithium iron phosphate positive active materials, the iron phosphate with the above structure can change the size, micromorphology and structure between the material particles, and obtain lithium iron phosphate positive active materials with high compaction density, high rate performance, high gram capacity and excellent cycle performance. No other equipment needs to be added, and it can be directly applied to existing general process equipment, and it has industrial production conditions; this method uses only one kind of iron phosphate to prepare high compaction and high rate products that require two or more iron phosphates in current industrial production, which simplifies the production steps and reduces the production cost, which meets the current general cost reduction needs of battery factories and car companies.

[0048] In the present application, the testing method for the specific surface area of ​​the modified material is the liquid nitrogen adsorption method.

[0049] As an example, the specific surface area of ​​the modified material can be 1200 m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g, etc., or may be within the range consisting of any of the above values.

[0050] The following is a detailed description of the method for preparing lithium iron phosphate positive electrode active materials provided by the present application. Figure 1 , the method comprising:

[0051] S10: Mix the iron source solution, phosphoric acid solution, oxidant, and modifying material to obtain a first slurry

[0052] According to some embodiments of the present application, the method for obtaining the iron source solution includes: mixing an untreated iron source solution, a phosphorus source solution, and a flocculant to obtain a pretreated mixed solution, adjusting the pH of the pretreated mixture to 2-4, filtering the precipitate, and obtaining the iron source solution, wherein the molar concentration of iron in the iron source solution is 1.5 mol / L-2 mol / L.

[0053] According to some embodiments of the present application, the method for obtaining the iron source solution includes:

[0054] S01: Preparation of untreated iron source solution

[0055] Specifically, the untreated iron source solution may be an untreated ferrous salt solution, which can be obtained by dissolving the ferrous salt in deionized water at 20° C. to 50° C. to a saturated state. The ferrous salt includes at least one of ferrous sulfate, ferrous chloride, and ferrous nitrate.

[0056] S02: Preparation of phosphorus source solution

[0057] Specifically, the phosphorus source solution is obtained by mixing 85% phosphoric acid and concentrated ammonia water. The amount of phosphoric acid added to the phosphorus source solution is 0.05%-0.25% of the mass of the ferrous salt added in step S01, and the amount of concentrated ammonia water added depends on the amount of phosphoric acid added. The concentrated ammonia water is mainly used to adjust the pH of the phosphorus source solution between 1-3.

[0058] S03: Solution purification

[0059] Specifically, an untreated iron source solution and a phosphorus source solution are mixed, a trace amount of ammonia water is added to the mixed solution to adjust the pH value to between 2 and 4, a flocculant solution is added, the amount of the flocculant solution added is 1%-3% of the mass of the mixed solution, and the mass concentration of the flocculant solution is 0.1%-0.2%, and finally the precipitation is filtered to obtain the purified iron source solution, and deionized water is added to dilute the purified ferrous solution to a concentration of 1.5 mol / L-2 mol / L.

[0060] As an example, the flocculant includes at least one of polyvinyl amide flocculant, polyacrylamide flocculant, and polydimethyldiallylammonium chloride.

[0061] According to some embodiments of the present application, the oxidant may be a mixed solution of 27% hydrogen peroxide and diammonium phosphate, the concentration of phosphorus in the diammonium phosphate solution is 1.5 mol / L-2.5 mol / L, and the addition of hydrogen peroxide maintains the concentration of phosphorus in the diammonium phosphate solution at 1 mol / L-2 mol / L.

[0062] According to some embodiments of the present application, the iron source solution obtained in step S03, the oxidant, 85% phosphoric acid solution, and the modifying material are mixed to obtain a first slurry.

[0063] According to some embodiments of the present application, the molar ratio of phosphorus element to iron element in the first slurry may be 1.1-1.25, for example, may be 1.1, 1.15, 1.2, 1.25, etc., or may be a range consisting of any of the above numerical values.

[0064] According to some embodiments of the present application, the content of trivalent iron in the first slurry is less than 10 ppm.

[0065] According to some embodiments of the present application, the specific surface area of ​​the modified material can be 1200m 2 / g-1400m 2 / g.

[0066] As an example, the modified material includes activated carbon with a mesh size of 800-1500.

[0067] As an example, the covalent organic framework material includes at least one of COF-5 and CTF-1.

[0068] According to some embodiments of the present application, based on the total mass of the first slurry, the mass proportion of the modified material can be 0.1%-0.3%, for example, 0.1%, 0.2%, 0.3%, etc., or can be a range composed of any of the above numerical values.

[0069] S20: heating and drying the first slurry to obtain a first intermediate product

[0070] According to some embodiments of the present application, the first slurry is heated, continuously stirred and kept warm, and crystallization is completed to form ferrous phosphate dihydrate slurry, which is then filtered and washed to obtain a filter cake, which is then dried to obtain a free moisture content of less than 4%.

[0071] According to some embodiments of the present application, the heating temperature may be 80° C.-90° C., and the heating time may be 2 h-5 h.

[0072] As an example, the heating temperature may be 80° C., 82° C., 84° C., 86° C., 88° C., 90° C., etc., or may be a range consisting of any of the above values.

[0073] As an example, the heating time may be 2 h, 3 h, 4 h, 5 h, etc., or may be a range consisting of any of the above values.

[0074] By making the heating temperature and time within the above ranges, the reactants in the first slurry will be mixed more evenly, the crystal transformation process will be gentler, and the crystal growth will be more consistent with the target.

[0075] S30: Sintering and crushing the first intermediate product for the first time to obtain iron phosphate

[0076] Specifically, the filter cake is placed in a muffle furnace for the first sintering. The first sintering process can completely burn off the modified material to obtain iron phosphate with a D50 of 2 μm-10 μm.

[0077] According to some embodiments of the present application, the temperature of the first sintering is 500° C.-700° C., and the time of the first sintering is 2 h-5 h.

[0078] As an example, the temperature of the first sintering may be 500° C., 550° C., 600° C., 650° C., 700° C., etc., or may be a range consisting of any of the above values.

[0079] As an example, the first sintering time may be 2 h, 3 h, 4 h, 5 h, etc., or may be within a range consisting of any of the above values.

[0080] By making the temperature and time of the first sintering within the above range, the modified material will be completely burned away, the formed iron phosphate structure framework will only partially collapse, and the rest will be completely retained, thereby forming two completely different microscopic particle morphologies.

[0081] According to some embodiments of the present application, the volume average particle size Dv50 of the iron phosphate is 2 μm-10 μm.

[0082] The Dv50 of iron phosphate can be measured by laser particle size analyzer (DLS).

[0083] According to some embodiments of the present application, the particle size distribution diagram of the iron phosphate presents a bimodal distribution.

[0084] According to some embodiments of the present application, the Fe / P of the iron phosphate is 0.95-0.99.

[0085] S40: Mix the iron phosphate, lithium source, carbon source, additives, and solvent to form a second slurry, and dry it to obtain a second intermediate product

[0086] According to some embodiments of the present application, the lithium source includes at least one of lithium hydroxide, lithium fluoride, lithium acetate, lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, lithium oxalate, and lithium nitrate.

[0087] According to some embodiments of the present application, the carbon source includes at least one of glucose, sucrose, acetylene black, starch, and cellulose.

[0088] According to some embodiments of the present application, the added amount of the carbon source is 6.5%-7.8% of the mass of the iron phosphate, for example, it can be 6.5%, 6.8%, 7.1%, 7.4%, 7.7%, 7.8%, etc., or it can be a range composed of any of the above values.

[0089] According to some embodiments of the present application, the additive includes a first additive and a second additive. The iron phosphate prepared by the method provided in the first aspect of the present application, the lithium source, the carbon source, the first additive, the second additive, and a solvent are mixed to form a slurry, which is then dried to obtain a second intermediate product.

[0090] As an example, the first additive includes at least one of compounds containing W, Mg, Nb, V, Ti, Mo, Rh, Os, and Ta elements.

[0091] As an example, the second additive includes at least one of industrial sodium hydroxide, polyacrylamide (PAM), industrial calcium chloride, and polyaluminum chloride.

[0092] According to some embodiments of the present application, the first additive accounts for 0.01%-0.5% of the mass of the iron phosphate, and the second additive accounts for 0.01%-0.5% of the mass of the iron phosphate.

[0093] Specifically, the first additive may account for 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc. of the mass of the iron phosphate, or may be within a range consisting of any of the above values.

[0094] Specifically, the second additive may account for 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc. of the mass of the iron phosphate, or may be within a range consisting of any of the above values.

[0095] According to some embodiments of the present application, the solid content of the second slurry may be 30%-50%, for example, 30%, 35%, 40%, 45%, 50%, etc., or may be a range consisting of any of the above numerical values.

[0096] According to some embodiments of the present application, the second slurry is ground and crushed, and the D50 of the slurry after grinding is controlled to be 0.3 μm-0.5 μm, and after spray drying, the D50 is 20 μm-40 μm.

[0097] S50: Sintering and crushing the second intermediate product under a protective atmosphere to obtain a lithium iron phosphate positive electrode active material

[0098] According to some embodiments of the present application, the second intermediate product is sintered for a second time under a protective atmosphere, and after air flow crushing, a lithium iron phosphate positive electrode active material is obtained, wherein the D50 of the lithium iron phosphate positive electrode active material is 0.9 μm-1.3 μm, and the compaction density is 2.58 g / cm 3 -2.64g / cm 3 .

[0099] According to some embodiments of the present application, the temperature of the second sintering may be 720°C-820°C, for example, 720°C, 750°C, 780°C, 810°C, 820°C, etc., or may be a range consisting of any of the above values.

[0100] According to some embodiments of the present application, the second sintering time may be 20h-30h, for example, 20h, 22h, 24h, 26h, 28h, 30h, etc., or may be a range consisting of any of the above numerical values.

[0101] By setting the temperature and time of the second sintering within the above ranges, lithium iron phosphate products with different compaction densities can be prepared and applied in different fields.

[0102] In summary, the method for preparing lithium iron phosphate positive electrode active materials proposed in this application has the following advantages:

[0103] By mixing the iron phosphate prepared in the present application with a lithium source, a carbon source, and an additive to prepare a lithium iron phosphate-based positive electrode active material, the size, micromorphology, and structure of the material particles can be changed to obtain a lithium iron phosphate-based positive electrode active material with a high compaction density, high rate performance, high gram capacity, and excellent cycle performance. No other equipment needs to be added, and the material can be directly applied to existing general process equipment, meeting the conditions for industrial production. The present method uses only one type of iron phosphate to prepare a high-compaction, high-rate product that currently requires two or more types of iron phosphates in industrial production, thereby simplifying the production steps and reducing the production cost, which meets the current general cost reduction needs of battery factories and automobile companies.

[0104] The third aspect of the present application provides a positive electrode plate, comprising the lithium iron phosphate type positive electrode active material provided in the first aspect of the present application or the lithium iron phosphate type positive electrode active material prepared by the method provided in the second aspect of the present application.

[0105] The fourth aspect of the present application provides a lithium secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.

[0106] The fifth aspect of the present application provides an electrical device, including the lithium secondary battery provided by the fourth aspect of the present application.

[0107] The electrical equipment may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0108] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0109] Example 1

[0110] (1) adding ferrous sulfate heptahydrate to deionized water at 40° C. and dissolving to saturation;

[0111] (2) taking 85% phosphoric acid solution, the phosphoric acid solution accounting for 0.1% of the mass of ferrous sulfate heptahydrate, and adding ammonia water to adjust the pH of the solution to 2.5-3.0;

[0112] (3) Mix (1) and (2), continue to add ammonia water to adjust the pH of the mixed solution to 3.0-3.5, add a poly(ethylene amide) flocculant solution with a mass concentration of 0.15%, and the amount of flocculant added is 1% of the mass of the mixed solution, and separate the solid and liquid to obtain a purified ferrous solution. Add pure water to control the concentration of ferrous sulfate to 1.65 mol / L;

[0113] (4) adding 27% hydrogen peroxide to a 1.9 mol / L ammonium dihydrogen phosphate solution to dilute the P element concentration to 1.7 mol / L;

[0114] (5) Add 0.1% of the mass of 13000 mesh activated carbon powder to the mixed solution in step (3), and then add 0.15 times the molar amount of ferrous sulfate phosphoric acid. Add an appropriate amount of the mixed solution in step (4) to control the molar ratio of phosphorus to iron in the solution to be 1.10 and the ferric iron content to be less than 10 ppm;

[0115] (6) The mixed solution of step (5) was reacted at 90°C for 4 hours, and then the reaction product was separated into solid and liquid. After washing, the solid product was dried and sintered in a muffle furnace at 600°C for 4 hours, and crushed to obtain a high-purity iron phosphate product with a bimodal particle size distribution. The SEN diagram of the iron phosphate is shown in the attached figure. Figure 2 and attached Figure 3 shown.

[0116] (7) The iron phosphate product obtained in step (6) is mixed with lithium carbonate, glucose, V2O5, TiO2, polyaluminium chloride and PEG1500 in pure water to obtain slurry A. The mass ratio of iron phosphate: lithium carbonate: glucose: pure water: V2O5: TiO2: polyaluminium chloride: PEG1500 is 4:1:0.3:2:0.0002:0.0002:0.0003:0.001.

[0117] (8) Grind until the D50 particle size of slurry A is 0.39 μm-0.40 μm. Then spray, and the D50 of the spray material is controlled at 25 μm-35 μm.

[0118] (9) Spray material sintering: the spray material was heated to 800 °C in a nitrogen atmosphere for 5 h, kept at 800 °C for 8.5 h, and then sintered using 10 m 3 / h nitrogen flow naturally cools down to 70℃ to obtain lithium iron phosphate particles. 1.05 V0.0015 Ti 0.002 Fe 0.9965 P 1.03 O4 / C positive electrode active material, D50 = 1.1 μm, SEM image as attached Figure 4 shown.

[0119] Example 2

[0120] (1) adding ferrous sulfate heptahydrate to deionized water at 40° C. and dissolving to saturation;

[0121] (2) taking 85% phosphoric acid solution, the phosphoric acid solution accounting for 0.1% of the mass of ferrous sulfate heptahydrate, and adding ammonia water to adjust the pH of the solution to 2.5-3.0;

[0122] (3) Mix (1) and (2), and continue to add ammonia water to adjust the pH of the mixed solution to 3.0-3.5. Add a polyacrylamide flocculant solution with a mass concentration of 0.15%, and the amount of flocculant added is 1% of the mass of the mixed solution, and separate the solid and liquid to obtain a purified ferrous solution. Add pure water to control the concentration of ferrous chloride to 1.5 mol / L;

[0123] (4) adding 27% hydrogen peroxide to a 2.0 mol / L ammonium dihydrogen phosphate solution to dilute the P element concentration to 1.7 mol / L;

[0124] (5) adding 0.1% of COF-5 powder to the mixed solution in step (3), followed by adding 0.15 times the molar amount of ferrous sulfate as phosphoric acid. Adding the mixed solution prepared in step (4), controlling the molar ratio of phosphorus to iron in the solution to be 1.20, and the content of trivalent iron to be less than 10 ppm;

[0125] (6) The mixed solution of step (5) was reacted at 90°C for 4 hours, and then the reaction product was separated into solid and liquid. After washing, the solid product was dried and sintered in a muffle furnace at 700°C for 4 hours, and crushed to obtain a high-purity iron phosphate product with a bimodal particle size distribution. The SEM image is shown in the attached figure. Figure 5 and Figure 6 shown.

[0126] (7) The iron phosphate product obtained in step (6) is mixed with lithium carbonate, glucose, V2O5, TiO2, polyaluminium chloride and PEG1500 in pure water to obtain slurry A. The mass ratio of iron phosphate: lithium carbonate: glucose: pure water: V2O5: TiO2: polyaluminium chloride: PEG1500 is 4:1:0.3:2:0.0002:0.0002:0.0003:0.001.

[0127] (8) Grind until the D50 particle size of slurry A is 0.38 μm-0.40 μm. Then spray, and the D50 of the spray material is controlled at 25 μm-35 μm.

[0128] (9) Spray material sintering: the spray material was heated to 800 °C in a nitrogen atmosphere for 5 h, kept at 800 °C for 8.5 h, and then sintered using 10 m 3 / h nitrogen flow naturally cools down to 70℃ to obtain lithium iron phosphate particles. 1.05 V 0.0015 Ti 0.002 Fe 0.9965 P 1.03 O4 / C positive electrode active material, D50 = 1.23 μm, SEM image as attached Figure 7 shown.

[0129] Example 3

[0130] (1) adding ferrous sulfate heptahydrate to deionized water at 40° C. and dissolving to saturation;

[0131] (2) taking 85% phosphoric acid solution, the phosphoric acid solution accounting for 0.1% of the mass of ferrous sulfate heptahydrate, and adding ammonia water to adjust the pH of the solution to 2.5-30;

[0132] (3) Mix (1) and (2), and continue to add ammonia water to adjust the pH of the mixed solution to 3.0-3.5. Add a poly(ethylene amide) flocculant solution with a mass concentration of 0.15%, and the amount of flocculant added is 1% of the mass of the mixed solution. Separate the solid and liquid to obtain a purified ferrous solution. Add pure water to control the concentration of ferrous sulfate to 1.65 mol / L;

[0133] (4) adding 27% hydrogen peroxide to a 1.9 mol / L ammonium dihydrogen phosphate solution to dilute the P element concentration to 1.7 mol / L;

[0134] (5) Add 0.1% of the mass of 15000 mesh activated carbon powder to the mixed solution in step (3), and then add 0.15 times the molar amount of ferrous sulfate phosphoric acid. Add an appropriate amount of the mixed solution in step (4) to control the molar ratio of phosphorus to iron in the solution to be 1.05 and the ferric iron content to be less than 10 ppm;

[0135] (6) The mixed solution of step (5) was reacted at 90°C for 4 hours, and then the reaction product was separated into solid and liquid. After washing, the solid product was dried and sintered in a muffle furnace at 600°C for 4 hours, and crushed to obtain a high-purity iron phosphate product with a bimodal particle size distribution. The SEM image of the iron phosphate is shown in the attached figure. Figure 8 shown.

[0136] (7) The iron phosphate product obtained in step (6) is mixed with lithium carbonate, glucose, V2O5, TiO2, polyaluminium chloride and PEG1500 in pure water to obtain slurry A. Furthermore, the mass ratio of iron phosphate: lithium carbonate: glucose: pure water: V2O5: TiO2: polyaluminium chloride: PEG1500 is 4:1:0.3:2:0.0002:0.0002:0.0003:0.001.

[0137] (8) Grind until the D50 particle size of slurry A is 0.39 μm-0.4 μm. Then spray, and the D50 of the spray material is controlled at 25 μm-35 μm.

[0138] (9) Spray material sintering: the spray material was heated to 800 °C in a nitrogen atmosphere for 5 h, kept at 800 °C for 8.5 h, and then sintered using 10 m 3 / h nitrogen flow naturally cools down to 70℃ to obtain lithium iron phosphate particles. 1.05 V 0.0015 Ti 0.002 Fe 0.9965 P 1.03 O4 / C positive electrode active material, D50 = 1.03 μm, SEM image as attached Fig. 9 shown.

[0139] The particle size test results of iron phosphate in Examples 1 to 3 are shown in the attached Fig.10 .

[0140] Comparative Example 1

[0141] (1) Add 0.15 times the molar amount of ferrous sulfate to a purified solution having a ferrous sulfate concentration of 1.65 mol / L with an 85% phosphoric acid solution.

[0142] (2) adding 27% hydrogen peroxide to a 1.9 mol / L diammonium phosphate solution to prepare a solution with a P element concentration of 1.7 mol / L;

[0143] (3) adding (2) dropwise to the mixed solution of (1), controlling the molar ratio of phosphorus to iron in the solution to be 1.10 and the content of trivalent iron to be less than 10 ppm;

[0144] (4) The mixed solution was reacted at 90°C for 4 h, and then the reaction product was separated into solid and liquid. After washing, the solid product was dried, sintered in a muffle furnace at 600°C for 4 h, and crushed to obtain an iron phosphate material. The SEM image is shown in the attached figure. Fig.11 Attached Fig.12 shown.

[0145] (5) The iron phosphate product is mixed with lithium carbonate, glucose, V2O5, TiO2, polyaluminium chloride and PEG1500 in pure water. The mass ratio of iron phosphate: lithium carbonate: glucose: pure water: V2O5: TiO2: polyaluminium chloride: PEG1500 is 4:1:0.3:2:0.0002:0.0002:0.0003:0.001.

[0146] (6) The finished lithium iron phosphate material is obtained by grinding, spraying, sintering and crushing. The grinding D50 particle size is 0.39μm-0.40μm. The spray material D50 is controlled at 25μm-35μm. The spray material is heated to 800℃ in a nitrogen atmosphere for 5 hours, kept at 800℃ for 8.5 hours, and then used for 10m 3 / h nitrogen flow naturally cools down to 70℃, and Li is obtained after air flow crushing 1.05 V 0.0015 Ti 0.002 Fe 0.9965 P 1.03 O4 / C positive electrode active material, D50 = 1.1μm-1.2μm, SEM picture as attached Fig.13 shown.

[0147] Comparative Example 2

[0148] (1) Select the ammonium method ferric phosphate material and the iron method ferric phosphate material sold on the market and mix them in a ratio of 1:1. The mixed ferric phosphate is mixed with lithium carbonate, glucose, V2O5, TiO2, polyaluminum chloride, and PEG1500 in pure water. The mass ratio of ferric phosphate: lithium carbonate: glucose: pure water: V2O5: TiO2: polyaluminum chloride: PEG1500 is 4:1:0.3:2:0.0002:0.0002:0.0003:0.001.

[0149] (2) The finished lithium iron phosphate material is obtained by grinding, spraying, sintering and crushing. The D50 particle size of the grinding material is 0.39μm-0.40μm. The D50 of the spray material is controlled at 25μm-35μm. The spray material is heated to 800℃ in a nitrogen atmosphere for 5 hours, kept at 800℃ for 8.5 hours, and then used for 10m 3 / h nitrogen flow naturally cools down to 70℃, and Li is obtained after air flow crushing 1.05 V 0.0015 Ti 0.002 Fe 0.9965 P 1.03 O4 / C positive electrode active material, D50=1.1μm-1.2μm.

[0150] Preparation of lithium secondary batteries

[0151] The lithium iron phosphate positive electrode active material, binder polyvinylidene fluoride (PVDF), and conductive carbon black in Examples 1 to 3, Comparative Example 1, and Comparative Example 2 were mixed in a ratio of 96.5:1.5:2 to prepare a positive electrode slurry with a solid content of 57%. The slurry was then mixed at 1500 rpm for 3 minutes and then mixed at 1200 rpm for 20 minutes. The slurry was evenly coated on a coater to a thickness of 250 μm, and then dried at 135°C for 30 minutes to control the surface density to 125±10 g / m 2 , continue to dry in a vacuum oven at 65℃ for 12h to obtain the electrode. Assemble the battery in the order of positive electrode shell → electrode → electrolyte → diaphragm → blotting paper → electrolyte → lithium sheet → nickel foam → electrolyte → negative electrode shell. The electrolyte is a mixture of ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) = 1:1:1, 1.1M LiPF6, 1.5% vinylene carbonate (VC) + 1.5% 1,3-propane sultone (PS). The battery was left to stand for 10h before testing, 0.5C constant current charging to 4.2V, then constant voltage charging to a cut-off current of 0.05C--standing (5min)--0.5C constant current discharge to 2.5V, and cycled twice.

[0152] Performance Testing

[0153] 1. Compacted density

[0154] Prepare 1g of sample, put it into a mold with a diameter of 13mm, use the Sansi Zongheng (UTM7305) compaction density meter, adjust the dynamometer pressure to 3KN, maintain the pressure for 30s, and then obtain the compaction density of the sample.

[0155] 2.0.5C discharge capacity

[0156] Charge at 0.5C constant current to 4.2V, then switch to constant voltage charging to a cut-off current of 0.05C, let stand (5min), and discharge at 0.5C constant current to 2.5V to get the 0.5C discharge capacity.

[0157] 3.0.5C platform retention rate

[0158] Charge at 0.5C constant current to 4.2V, then switch to constant voltage charging to a cut-off current of 0.05C, let stand (5min), and discharge at 0.5C constant current to 2.5V. During the discharge process, the time the battery is above 3.2V is divided by the total discharge time × 100%.

[0159] 4. Energy efficiency

[0160] Charge at 0.5C constant current to 4.2V, then charge at constant voltage to a cut-off current of 0.05C, let stand (5min), and discharge at 0.5C constant current to 2.5V. Energy efficiency can be obtained by multiplying discharge capacity × discharge time / (charge capacity × constant current charge time) × 100%.

[0161] 5. Constant current charging ratio

[0162] Charge at 0.5C constant current to 4.2V, then switch to constant voltage charging to a cut-off current of 0.05C. Divide the charging capacitance of the constant current section by the total charging capacitance × 100% to get the constant current charging ratio.

[0163] The test results of the batteries formed by the lithium iron phosphate positive electrode active materials in Examples 1 to 3, Comparative Example 1 and Comparative Example 3 are shown in Table 1.

[0164] Table 1

[0165]

[0166]

[0167] It can be seen from the comparison between Examples 1 to 3 and Comparative Examples 1 and 2 that the lithium iron phosphate-based positive electrode active material prepared by the examples of the present application can improve the discharge capacity and coulombic efficiency of the battery.

[0168] By the attached Figure 2 -Attached Fig. 9 With attached Fig.11 -Attached Fig.13 By comparison, it can be seen that the iron phosphate prepared in Examples 1 to 3 presents two forms, fluffy porous and non-porous, in the SEM images compared with the iron phosphate prepared in the comparative example.

[0169] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0170] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A lithium iron phosphate positive electrode active material, characterized in that: Including compounds shown in formula I: Li a M 1-b Me b P c O4 / C type Ι, Wherein, 0.9≤a≤1.1, 0.98≤b<1, 0.96≤b / c≤0.99, Me includes at least one element selected from Mn, Co, Ni, and Fe, and M includes at least one element selected from W, Mg, Nb, V, Ti, Mo, Rh, Os, and Ta; The D50 of the lithium iron phosphate positive electrode active material is 0.9 μm-1.3 μm, and the compaction density of the lithium iron phosphate positive electrode active material is 2.58 g / cm 3 -2.64g / cm 3 .

2. A method for preparing the lithium iron phosphate positive electrode active material according to claim 1, characterized in that: include: The iron source solution, phosphoric acid solution, oxidant and modifying material are mixed to obtain a first slurry, wherein the modifying material has a specific surface area of ​​1200 m 2 / g-1600m 2 / g, the modified material includes at least one of activated carbon, graphene, and a covalent organic framework material; Heating and drying the first slurry to obtain a first intermediate product; The first intermediate product is subjected to a first sintering and crushing to obtain iron phosphate; The iron phosphate, lithium source, carbon source, additive and solvent are mixed to form a second slurry, and dried to obtain a second intermediate product; The second intermediate product is subjected to a second sintering under a protective atmosphere, wherein the temperature of the second sintering is higher than the temperature of the first sintering, and is crushed to obtain the lithium iron phosphate-based positive electrode active material.

3. The method according to claim 2, characterized in that The specific surface area of ​​the modified material is 1200m 2 / g-1400m 2 / g.

4. The method according to claim 2, characterized in that: Based on the total mass of the first slurry, the mass proportion of the modified material is 0.1%-0.3%.

5. The method according to claim 2, characterized in that: The activated carbon includes activated carbon with a mesh size of 800-1500; and / or the covalent organic framework material includes at least one of COF-5 and CTF-1.

6. The method according to any one of claims 2 to 5, characterized in that: Satisfy at least one of the following conditions: The heating temperature is 80°C-90°C, and the heating time is 2h-5h; The temperature of the first sintering is 500° C.-700° C., and the time of the first sintering is 2 h-5 h.

7. The method according to any one of claims 2 to 5, characterized in that: The method for obtaining the iron source solution comprises: Untreated iron source solution, phosphorus source solution and flocculant are mixed to obtain a pretreated mixed solution, the pH of the pretreated mixture is adjusted to 2-4, and the precipitate is filtered to obtain the iron source solution, wherein the molar concentration of iron in the iron source solution is 1.5 mol / L-2 mol / L.

8. The method according to any one of claims 2 to 5, characterized in that: The molar ratio of phosphorus element to iron element in the first slurry is 1.1-1.

25.

9. The method according to any one of claims 2 to 5, characterized in that: The iron phosphate satisfies at least one of the following conditions: The volume average particle size Dv50 of the iron phosphate is 2 μm-10 μm; The particle size distribution diagram of the iron phosphate presents a bimodal distribution; The Fe / P of the ferric phosphate is 0.95-0.

99.

10. The method according to any one of claims 2 to 5, characterized in that: The temperature of the second sintering is 720° C.-820° C., and the time of the second sintering is 20 h-30 h.

11. A positive electrode sheet, characterized in that: The invention comprises the lithium iron phosphate positive electrode active material as described in claim 1 or the lithium iron phosphate positive electrode active material prepared by the method as described in any one of claims 2-10.

12. A lithium secondary battery, characterized in that: Including the positive electrode sheet as claimed in claim 11.

13. An electrical equipment, characterized in that: Includes the lithium secondary battery as claimed in claim 12.